Eastern Mediterranean foraminiferal palaeoecological response to Mid-Late Pliocene climatic regime: A preliminary note. - Drinia, H.; Antonarakou, A.; Mihalakopoulos, S.; Tsiolakis, E. (Bulletin of the Geological Society of Greece, 2013)
The main objective of this work is to investigate the climatic influence on the sedimentation during mid to late Pliocene in Cyprus island. For this reason, a section located in Pissouri sub-basin, southern Cyprus, was chosen to be studied. The section comprises a nearly uninterrupted succession of marine sediments, dominated by grey marls, which are cyclically alternating with yellowish silty marls. The identification of age diagnostic planktonic foraminifera suggests a mid to upper Pliocene age. The calculated faunal parameters document cyclic fluctuations consistent with shifts in such climate belts. A good age resolution of the cycles and an indication of sedimentation rate would be required in order to connect cyclicity to orbital perturbations.